Effect of Chromium, Cadmium and Arsenic on Growth and Morphology of HeLa Cells - Ahmad, Aftab; Muneer, Bushra; Shakoor, Abdul Rauf (Journal of Basic & Applied Sciences, 2012)
Rapid industrialization and anthropogenic activities are main causes of environmental pollution and level of heavy metals is on the increase in biosphere. These heavy metals have deleterious effects on human health and cause many abnormalities. In the present study, we investigated the effects of arsenic, chromium and cadmium on the growth and morphology of HeLa cell. The total protein profile of control as well as treated cells was checked by SDS-PAGE. Chromium was used to induce the expression of metallothionein protein and expression of protein was detected by SDSPAGE. There was reduction in proliferation of cells in chromium, cadmium and arsenic containing medium. Cell necrosis was observed with the increase in the concentration of chromium and at 0.10 µg/mL concentration of chromium complete cell lysis was observed. There was change in morphology of cells with increase in concentration of cadmium and at 1.0 µg/ml cells became round. Arsenic also proved to be deleterious for the growth of HeLa cells and there was change in morphology of cells at 1.0 µg/ml but it was not as toxic as chromium and cadmium. There was no difference in protein profile of control and chromium treated cells except lower in concentration of protein due to less number of cells. Metallothionein were not observed in treated cells by SDS-PAGE. Heavy metal have very deleterious effects on human cells and with increase in metal concentration there was change in morphology of cells and also great reduction in proliferation